Making the modern primitive cultural tourism in the Trobriand Islands - MacCarthy, Michelle 1976- (University of Hawaiʻi Press, 2016)
This book provides an anthropological analysis of the encounter between local residents and tourists in the Trobriand Islands, a place renowned in anthropology and represented in various media as "culturally authentic." In such a place, how are ideas about authenticity implicated in creating and representing the self and cultural Others in the context of cultural tourism? To answer this question, the author examines four arenas of interaction between Trobriand Islanders and tourists: formal performances, informal village visits, souvenir shopping, and tourist photography. She employs symbolic/interpretive approaches and concepts drawn from economic anthropology to examine the relationship of tourism to the commoditization of culture, the ways in which local residents actively represent and enact "Trobriandness," and the ways tourists interpret and narrate their experience